Limb Amputation 2020
DOI: 10.5772/intechopen.90532
|View full text |Cite
|
Sign up to set email alerts
|

Stump Overgrowth after Limb Amputation in Children

Abstract: Stump overgrowth is the most common complication after limb amputation in children. Its morbidity is relatively high, that required frequent revisions of the stump and prosthesis. The incidence of stump overgrowth varies in the literature; depending on different factors. The exact pathogenesis is unclear, many hypotheses have been suggested. The treatment is a challenge; simple excision of the bone is associated with recurrence and further shorting of the stump. Many options of treatment have been used. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Of note, the authors included individuals of all age groups, while most of them had an age ranging between 41 and 50 years. Similar to the previous study, Jahmani et al [ 5 ] reported diabetic foot (41.9%) and trauma (38.4%) as leading indications for amputation. The authors studied indications for lower-limb amputation in patients with (0-10) and (11-20) years of age, of which primary bone cancer and trauma were reported as the common indication for amputation within each of these age groups, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Of note, the authors included individuals of all age groups, while most of them had an age ranging between 41 and 50 years. Similar to the previous study, Jahmani et al [ 5 ] reported diabetic foot (41.9%) and trauma (38.4%) as leading indications for amputation. The authors studied indications for lower-limb amputation in patients with (0-10) and (11-20) years of age, of which primary bone cancer and trauma were reported as the common indication for amputation within each of these age groups, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, peripheral vascular affection is perceived as the leading cause of amputation in developed countries, while trauma, infection, and malignant tumors are reported as leading causes for major limb amputation in developing countries [3,4]. Although lower-limb amputations in pediatrics is rare, they are often associated with several complications, mostly being bone overgrowth regarding the amputated end of the limb and leading to permanent internal penetration of soft tissue under load, making prosthetic use impossible [5]. Another observed complication is the formation of a sharpended spur that potentially penetrates overlying soft tissue due to continuous growth, particularly in transfemoral (TF) and transtibial (TT) amputation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bony overgrowth leads to bursa formation and, in severe cases, can perforate the skin. Historically, the treatment of bony overgrowth of very short residual limbs consisted of prosthetic modifications and various skin traction methods developed by Marquardt that were particularly cumbersome with limited success 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Although synthetic caps can successfully reduce bony overgrowth, they have been associated with failure of fixation leading to infection, implant fracture, and subsequent pain with revision rates for polyethylene and Teflon caps as high as 70% and 29%, respectively 10 . While Teflon caps have failure rates similar to those of bone grafts, they are associated with more complications such as infection, inflammation, and painful bursa formation compared with other synthetic materials 1,2 .…”
Section: Discussionmentioning
confidence: 99%